Demographics, Pattern of Care, and Outcome Analysis of Malignant Melanomas - Experience From a Tertiary Cancer Centre in India - Bajpai, Jyoti; Abraham, George; Saklani, Avanish P.; Agarwal, Anshul; Das, Sashanka; Chatterjee, Ambarish; Kapoor, Akhil; Eaga, Prathyusha; Mondal, Pradip Kumar; Chandrasekharan, Arun; Bhargava, Prabhat Ghanshyam; Srinivas, Sujay; et al. (Frontiers in Oncology, 2021)
Background Treatment of malignant melanoma has undergone a paradigm shift with the advent of immune checkpoint inhibitors (ICI) and targeted therapies. However, access to ICI is limited in low-middle income countries (LMICs). Patients and Methods Histologically confirmed malignant melanoma cases registered from 2013 to 2019 were analysed for pattern of care, safety, and efficacy of systemic therapies (ST). Results There were 659 patients with a median age of 53 (range 44–63) years; 58.9% were males; 55.2% were mucosal melanomas. Most common primary sites were extremities (36.6%) and anorectum (31.4%). Nearly 10.8% of the metastatic cohort were BRAF mutated. Among 368 non-metastatic patients (172 prior treated, 185 de novo, and 11 unresectable), with a median follow-up of 26 months (0–83 months), median EFS and OS were 29.5 (95% CI: 22–40) and 33.3 (95% CI: 29.5–41.2) months, respectively. In the metastatic cohort, with a median follow up of 24 (0–85) months, the median EFS for BSC was 3.1 (95% CI 1.9–4.8) months versus 3.98 (95% CI 3.2–4.7) months with any ST (HR: 0.69, 95% CI: 0.52–0.92; P = 0.011). The median OS was 3.9 (95% CI 3.3–6.4) months for BSC alone versus 12.0 (95% CI 10.5–15.1) months in any ST (HR: 0.38, 95% CI: 0.28–0.50; P < 0.001). The disease control rate was 51.55%. Commonest grade 3–4 toxicity was anemia with chemotherapy (9.5%) and ICI (8.8%). In multivariate analysis, any ST received had a better prognostic impact in the metastatic cohort. Conclusions Large real-world data reflects the treatment patterns adopted in LMIC for melanomas and poor access to expensive, standard of care therapies. Other systemic therapies provide meaningful clinical benefit and are worth exploring especially when the standard therapies are challenging to administer.